PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN CENGKARENG JAKARTA BARAT - Sazly, Syukron; Winna, Winna (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
Abstract Work Discipline is directly related to employee performance. Work discipline perceived directly by employees can reduce performance or improve employee performance. Employees who feel disciplined about the work they get will have an impact on the overall performance of a goverment agency. The method of data collection are observations, litteratures study, documentations study  and questionnaires spread over. The research methods used is descriptive quantitative analysis method that aims to know whether there is influence of work discipline on employee performance. The reseach was held at April 30, 2018 untill May 30, 2018. Test of research instrument using IBM SPPS 22 program. Data from 30 questionnaires distributed to respondents is primary data source. Based on the result ofthis research, the correlation test is strongly correlated caused exists at interval of 0,600-0,799, that means  r table> r count at 0,644> 0,361. The result also indicates that there is an influence of work discipline to the performance of 41.4% on one hand and and diother hand,  the rest of 58.6% influenced by other factors not examined the author. So, based on the results of the regression test can be concluded that the discipline of work have a significant and strong effect on employee performance who work at the office of Kecamatan Cengkareng – Jakarta Barat.Key word: Work Discipline, Work Performance,  Employee Performance